HOMESICKNESS AND DEPRESSION RISK AMONG UNDERGRADUATE HEALTH SCIENCE STUDENTS IN A THAI UNIVERSITY: A CROSS-SECTIONAL STUDY - Ounprasertsuk, Jatuporn; Wannapaschaiyong, Prakasit; Tipwong, Araya (Malaysian Journal of Public Health Medicine, 2026)
Homesickness is a common psychological issue among university students living away from home, impacting their mental health and academic performance. Studies have shown a higher risk of depression linked to homesickness. This study investigates the levels of homesickness, the risk of depression, and their relationship among health science students in Thailand. A descriptive cross-sectional study was conducted from October 2023 to March 2024, involving a total of 291 students selected through proportional stratified sampling. Data were gathered using self-administered questionnaires and analyzed employing descriptive statistics and Pearson's correlation coefficient. The results indicated that 78.1% of participants experienced moderate homesickness, 19.2% reported low homesickness, and 2.7% faced severe homesickness. In terms of depression risk, 48.5% reported very low risk and 34.0% reported low risk of depression, 13.0% exhibited a moderate risk, while 4.5% were classified as having a severe risk. A significant positive correlation was observed between total homesickness scores and depression risk (r = 0.357, p < 0.001). Among the various dimensions of homesickness, the loss of self aspect showed the strongest association with depression risk (r = 0.482, p < 0.01), highlighting its critical role in the connection between homesickness and mental health issues. This study emphasizes the high prevalence of moderate homesickness among university students, alongside a majority reporting very low to low depression risk. The significant relationship between homesickness and depression, particularly through the loss of self dimension, suggests the necessity for university mental health programs to implement early screening and targeted interventions to address these intertwined challenges.